Sinking Brain: Unusual Cause of Orthostatic Headache - Raina R; Kaushik M; Mahajan SK; Sondhi S; Banayal V; Sharma JB (Online Journal of Health & Allied Sciences, 2015)
We report a case presenting with an orthostatic headache. Brain magnetic resonance imaging (MRI) revealed typical pachymeningeal enhancement. CT myelography revealed leakage at the thoracic level. Patient was successfully treated by lumbar epidural blood patch (EBP).